The Effect of Education, Health, Minimum Wage, Foreign Investment on Labor Productivity in 33 Provinces of Indonesia - Nia Rizky Maharani; Nenik Woyanti (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The competitiveness of labor is a key factor to encourage the competitiveness of a country's economy. Indonesia has low labor competitiveness due to uncompetitive labor productivity. In addition, Indonesia has a trend of declining labor productivity growth, so more serious attention is needed to make labor productivity better. This study aims to analyze the effect of education, health, minimum wage, and foreign investment on labor productivity using panel data from 33 provinces of Indonesia in 2010-2019. This research used a multiple linear regression FEM with cross-section weight and coefficient covariance method cross-section SUR (PSCE). The result proved partially, health and minimum wage have a significant positive effect, while education and foreign investment have an insignificant positive effect on labor productivity. The most dominant independent variable is health. Simultaneously, the four independent variables have a significant effect on labor productivity in 33 provinces of Indonesia